The Afghan - Forsyth, Frederick 1938- (Corgi Books, 2007)
"When British and American intelligence catch wind of a major Al Qaeda operation in the works, they instantly galvanize--but to do what? They know nothing about it: the what, where, or when. They have no sources in Al Qaeda, and it's impossible to plant someone. Impossible, unless-- The Afghan is Izmat Khan, a five-year prisoner of Guanta?namo Bay and a former senior commander of the Taliban. The Afghan is also Colonel Mike Martin, a twenty-five-year veteran of war zones around the world--a dark, lean man born and raised in Iraq. In an attempt to stave off disaster, the intelligence agencies will try to do what no one has ever done before--pass off a Westerner as an Arab among Arabs.--From publisher description."--From source other than the Library of Congress